The evolution of dynamic energy during drop hammer testing of Brazilian disk with non-persistent joints: An extensive experimental investigation. (February 2022) - Shakeri, Jamshid; Asadizadeh, Mostafa; Babanouri, Nima; Nowak, Samuel; Sherizadeh, Taghi
Highlights: As the joint continuity factor increases, the required D ynamic E nergy for C rack I nitiation ( DECI ) and D ynamic E nergy for C rack C oalescence ( DECC ) decrease. DECI and DECC decrease by increasing joint spacing up to its middle level and then increase as the joint spacing increases. The bridge angle and loading direction do not affect DECI, but by increasing bridge angle DECC decreases, and it increases by increasing loading direction angle. Joint spacing and joint continuity factors significantly affect DECI, and joint continuity factor and loading direction have significant effect on DECC . Abstract: Rock mass is well known as a discontinuous, heterogeneous, and anisotropic material. The behavior and strength of rock mass is heavily controlled by the condition and orientation of discontinuities (faults, joints, bedding planes) and discontinuity sets. Under dynamic loading conditions, rock bridges along non-persistent discontinuity planes may crack, and a fully persistent discontinuity may form, potentially affecting the stability of a rock structure. The study of the dynamic behavior of rock discontinuities has critical implications for civil engineering, the mining industry, and any other areas where rock mass is utilized as a structural foundation in areas prone to dynamic loading conditions, such as those formed during earthquake events. In this paper, cement-mortar-based Brazilian disks containing open, non-persistent joints were constructed and subjected to impact loading to investigate their impact energy behavior. The effect of some parameters, such as joint continuity factor (the relationship between joint length and rock bridge length), bridge angle, joint spacing, joint orientation, and impact angle were investigated to estimate the required D ynamic E nergy for C rack I nitiation ( DECI ), D ynamic E nergy for C rack C oalescence ( DECC ) and failure pattern of specimens. The results of the experiments revealed an increasingly continuous joint reduces the DECI and DECC, while larger joint spacings past the middle value of those experimented increase the DECI and DECC. The bridge angle and loading direction do not affect DECI, but by increasing bridge angle DECC decreases, and it increases by increasing loading direction angle. Finally, an optimization analysis was conducted which showed that joint spacing and joint continuity factors significantly affects DECI, and joint continuity factor and loading direction have significant effect on DECC .